CaM Kinase II mediates maladaptive post‐infarct remodeling and pro‐inflammatory chemoattractant signaling but not acute myocardial ischemia/reperfusion injury. Issue 10 (5th September 2014) - Weinreuter, Martin; Kreusser, Michael M; Beckendorf, Jan; Schreiter, Friederike C; Leuschner, Florian; Lehmann, Lorenz H; Hofmann, Kai P; Rostosky, Julia S; Diemert, Nathalie; Xu, Chang; Volz, Hans Christian; Jungmann, Andreas; et al.
Abstract CaMKII was suggested to mediate ischemic myocardial injury and adverse cardiac remodeling. Here, we investigated the roles of different CaMKII isoforms and splice variants in ischemia/reperfusion (I/R) injury by the use of new genetic CaMKII mouse models. Although CaMKIIδC was upregulated 1 day after I/R injury, cardiac damage 1 day after I/R was neither affected in CaMKIIδ‐deficient mice, CaMKIIδ‐deficient mice in which the splice variants CaMKIIδB and C were re‐expressed, nor in cardiomyocyte‐specific CaMKIIδ/γ double knockout mice (DKO). In contrast, 5 weeks after I/R, DKO mice were protected against extensive scar formation and cardiac dysfunction, which was associated with reduced leukocyte infiltration and attenuated expression of members of the chemokine (C‐C motif) ligand family, in particular CCL3 (macrophage inflammatory protein‐1α, MIP‐1α). Intriguingly, CaMKII was sufficient and required to induce CCL3 expression in isolated cardiomyocytes, indicating a cardiomyocyte autonomous effect. We propose that CaMKII‐dependent chemoattractant signaling explains the effects on post‐I/R remodeling. Taken together, we demonstrate that CaMKII is not critically involved in acute I/R‐induced damage but in the process of post‐infarct remodeling and inflammatory processes.